Parameters Used For Objective Acoustic Vocal Analysis In Paediatric Patients with Bronchiectasis - Faruk Calim, Omer; Selim Yıldırım, Yavuz; Gedik, Özge; Çakır, Erkan; Özturan, Orhan (ENT Updates, 2019)
Objectives: Bronchiectasis typically manifests with persistent coughing, pus-filled discharge, lethargy, dyspnoea, sternal pain, haemoptysis and dilated airways. Such symptoms can adversely affect the quality of life and voice characteristics of sufferers from bronchiectasis. This study had as its objective the objective comparison of vocal differences between healthy children and those with bronchiectasis. Methods: The parameters examined were jitter, percentage jitter, shimmer, noise-to-harmonics ratio (NHR), voice turbulence index (VTI), and soft phonation index (SPI). Data from the cases and controls were compared by means of paired t-tests. Results: The mean age for the cases was 11.53 years. In terms of absolute jitter, percentage jitter, shimmer and SPI, no differences were detected at the level of statistical significance. However, the NHR and VTI did differ between cases and controls at the level of statistical significance. Conclusion: The research reveals that an holistic approach has an influence on patient outcomes. Sufferers from bronchiectasis experience vocal alterations, especially with respect to NHR and VTI, the values of which were raised in comparison with healthy controls.